2012
DOI: 10.1098/rspb.2012.0893
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up effects of host-plant species diversity and top-down effects of ants interactively increase plant performance

Abstract: While plant diversity is well known to increase primary productivity, whether these bottom-up effects are enhanced by reciprocal top-down effects from the third trophic level is unknown. We studied whether pine tree species diversity, aphid-tending ants and their interaction determined plant performance and arthropod community structure. Plant diversity had a positive effect on aphids, but only in the presence of mutualistic ants, leading to a threefold greater number of both groups in the tri-specific culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 48 publications
(73 reference statements)
1
77
2
1
Order By: Relevance
“…Most studies have been restricted to measuring plant diversity-mediated effects on predator or parasitoid abundance and diversity [2,6,13,20,48,49] as well as predation or parasitism rates [20], but almost no studies have documented the consequences of such effects on herbivory and plant growth. One exception is a recent study by Moreira et al [7] showing that higher recruitment of predatory ants with increasing plant species diversity resulted in positive direct and indirect effects of ants on aphids and plant growth, respectively. Similarly, Haddad et al [2] reported for a temperate grassland that higher primary production with increasing plant diversity was associated with a substantial increase in the ratio of natural enemy (predators, parasitoids) to herbivore abundance in diverse plant patches.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 97%
See 2 more Smart Citations
“…Most studies have been restricted to measuring plant diversity-mediated effects on predator or parasitoid abundance and diversity [2,6,13,20,48,49] as well as predation or parasitism rates [20], but almost no studies have documented the consequences of such effects on herbivory and plant growth. One exception is a recent study by Moreira et al [7] showing that higher recruitment of predatory ants with increasing plant species diversity resulted in positive direct and indirect effects of ants on aphids and plant growth, respectively. Similarly, Haddad et al [2] reported for a temperate grassland that higher primary production with increasing plant diversity was associated with a substantial increase in the ratio of natural enemy (predators, parasitoids) to herbivore abundance in diverse plant patches.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 97%
“…Interestingly, some of the previously described studies addressing feedbacks (e.g. [7]) looked at effects of ants, a particularly important group of predatory omnivores which may in some cases act as herbivore mutualists. In this sense, we note that although there are a vast number of studies on the effects of diversity on enemies of herbivores, almost no attention has been given to herbivore mutualists.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in the study of plant diversity effects on food web dynamics [4,6,10], the relative importance of these two mechanisms remains understudied. Here, we investigated the bottom-up effects of plant genetic diversity on multi-trophic communities and the mechanistic pathways by which plant genetic diversity may vary in their influence on interactions between higher trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…enemies and mutualists of herbivores (see [3,4,10], and the scheme represented in figure 1). The pathways for plant diversity to affect herbivore enemies or mutualists can be classified into two types [11].…”
Section: Introductionmentioning
confidence: 99%